IMPROVING STUDENTS SPEAKING ABILITY BY USING MICROSOFT POWER POINT OF THE TOURISM STUDY PROGRAM - Bahri, Syarlly; Susilawati, Endang; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract: The goal of this Classroom Action Research (CAR) was to answer the research problem that is â€œHow well does the studentsâ€™ speaking ability improvement in pronunciation, grammar and vocabulary and speaking problem like inhibition, taking too long compose to utterances and low or uneven participation minimize after being conducting visual media group presentation of the twelve grade B students of SMK Negeri 1 Pontianak in academic year 2012/2013?â€. To improve studentsâ€™ speaking ability, the researcher conducted a Classroom Action Research. The total number of the XI classâ€™ students is 25 students. Then, the data of this research were taken from studentsâ€™ score in two cycles and they were collected by using observation and measurement techniques. Based on the research finding, it could be seen that the studentsâ€™ mean score in the second cycle (66.52) was higher than the first cycles (59.96). Specifically, the application of the visual media group presentation for teaching speaking skills has a significant result. The pronunciation component in the first cycle is 23.64 from the maximum score 40 increases to 27.44, increasing 3.80. The grammar component in first cycle is 19.84 from the maximum score 35 increases to 21.48, increasing 1.64 The vocabulary component shows 16.48 in the first cycle increases to 17.60 in the second cycle form the maximum score 25, increasing 1.12.Â  In short, the action hypothesis is accepted.Keywords: Power Point, Speaking, Tourism Study